Microsoft office 2000 simplified the new features - Palani Murugappan (Simplified Microsoft 2000 series ;, 2000)
This book assumes you know the basics of operating a PC with Windows 95/98. If the guides you step-by-step to comprehenf some of new features of Office 2000 beginning with the global features, moving on Word, Excell and PowerPoint 2000.